34.4: Multi‐functional Automotive Information Integrated System for CID. (28th November 2018) - Wang, Yaoyao; Yu, Jie; Sun, Pai; Ren, Fujian; Wang, Xiaoxia; Han, Rui; Ma, Qing; Yoon, Daekeun; Chen, Ming
Abstract : BOE has made 12.8 inch automotive information integrated system for CID. The FPD LINK III has been used for long distance transmission. The function of Gesture, Touch and Haptic Feedback has also been integrated in the 12.8 inch automotive CID. In order to make the produce lighter and thinner, the integrated design of middle frame and rear cover has been used.